MENJADI ASN CERDAS FINANSIAL: STRATEGI PENGELOLAAN KEUANGAN UNTUK KESEJAHTERAAN BERKELANJUTAN - Puryandani, Siti; Purnomo, Dwi Tjahjo (Sekolah Tinggi Ilmu Ekonomi AMA, 2026)
This community service program aims to enhance financial literacy and promote effective financial management strategies among civil servants (ASN) to achieve sustainable well-being. Despite having relatively stable income sources, many ASN still face financial challenges due to limited financial planning, consumptive behaviour, and lack of understanding of investment and risk management. The program employed an educational and participatory approach through training sessions, discussions, and practical exercises on budgeting, cash flow management, debt control, and basic investment planning. The results indicate a significant improvement in participants’ understanding of personal financial management, particularly in prioritizing needs over wants, preparing structured financial plans, and recognizing the importance of emergency funds and financial protection. Participants also demonstrated increased awareness of long-term financial goals, including retirement planning. Behavioural changes were observed in the form of improved financial discipline, such as routine expense recording and consistent saving habits. However, challenges remain, including limited time for implementation and the persistence of consumptive patterns. Therefore, continuous mentoring and the integration of digital financial tools are recommended to ensure sustainability. Overall, this program contributes to fostering financially responsible behaviour among ASN, supporting their long-term welfare and professional performance.